Stable money and central bank independence: Implementing monetary institutions in postwar Germany - Carsten Hefeker (Philipps-University Marburg, School of Business and Economics, 2019)
Germany prides itself in having one of the most successful central banks and currencies with respect to independence and stability. I show that not only were both imposed on the country after 1945 but that there was also initial resistance to both among German experts and officials. This was then a rare case of successful imposition of institutions from abroad. Events are discussed in light of Peter Bernholz's requirements for stable money and a successful central bank.
Keywords: E42; E58; N14; N24; 330; Currency reform; Bundesbank; central bank independence; institutional reform